2020
DOI: 10.3390/ijms21062101
|View full text |Cite
|
Sign up to set email alerts
|

Different Trafficking Phenotypes of Niemann-Pick C1 Gene Mutations Correlate with Various Alterations in Lipid Storage, Membrane Composition and Miglustat Amenability

Abstract: Niemann-Pick Type C (NPC) is an autosomal recessive lysosomal storage disease leading to progressive neurodegeneration. Mutations in the NPC1 gene, which accounts for 95% of the cases, lead to a defect in intra-lysosomal trafficking of cholesterol and an accumulation of storage material including cholesterol and sphingolipids in the endo-lysosomal system. Symptoms are progressive neurological and visceral deterioration, with variable onset and severity of the disease. This study investigates the influence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The disruption of LRs distribution induced by DSS is mainly attributed to the decrease of cholesterol level in LRs [ 9 ]. This result is also in line with pervious observations in which we have demonstrated a subtle reduction in the intensity of FLOT2 in the top fraction of LRs upon treatment of fibroblasts with N-butyl-deoxynojirimycin (known as miglustat), which inhibits sphingolipid synthesis and thus alters the composition of LRs in these cells [ 59 ]. The effect of RCME is likely linked to its phenolic composition, specifically luteolin [ 60 ], which has the capacity to inhibit lipid peroxidation that occurs in experimental colitis induced by DSS [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…The disruption of LRs distribution induced by DSS is mainly attributed to the decrease of cholesterol level in LRs [ 9 ]. This result is also in line with pervious observations in which we have demonstrated a subtle reduction in the intensity of FLOT2 in the top fraction of LRs upon treatment of fibroblasts with N-butyl-deoxynojirimycin (known as miglustat), which inhibits sphingolipid synthesis and thus alters the composition of LRs in these cells [ 59 ]. The effect of RCME is likely linked to its phenolic composition, specifically luteolin [ 60 ], which has the capacity to inhibit lipid peroxidation that occurs in experimental colitis induced by DSS [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…Taking all this together, it can be postulated that an impaired trafficking of LR-enriched vesicles harboring SI—and other membrane proteins—and their intracellular retention leads to an intracellular accumulation of the two main lipid components comprising LRs, cholesterol, and sphingolipids. This in turn could elicit redistribution and alterations in the membrane lipid composition as has been demonstrated in several lysosomal storage diseases, such as Niemann-Pick Type C and Fabry diseases ( Brogden et al, 2017 , 2020 ; Shammas et al, 2019 ). In addition to altered membrane and protein trafficking in infected Caco-2 cells, S. aureus infection resulted in a reduction of the overall enzymatic activity of SI, most likely due to altered LRs.…”
Section: Discussionmentioning
confidence: 94%
“…However, recent studies identified “cholesterol auxotrophy”, the inability to survive without exogenous cholesterol, in varying cancer subtypes (27,28) and suggest cholesterol uptake as a targetable pathway. NPC1 specifically transports lysosomal cholesterol to the endoplasmic reticulum (29) where cellular cholesterol levels are sensed and controlled (17,30) . By depleting the endoplasmic reticulum of cholesterol, NPC1 inhibition affects both supply of exogenous cholesterol as well and disrupts cholesterol homeostasis (29,31) .…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies identified "cholesterol auxotrophy", the inability to survive without exogenous cholesterol, in varying types of cancer (27,28) ,suggesting cholesterol uptake as a targetable pathway. NPC1 specifically transports lysosomal cholesterol to the endoplasmic reticulum (29) where cellular cholesterol levels are sensed and controlled (17,30) .…”
Section: Tnbc Cells Are Cholesterol Auxotrophs But Do Not Solely Depe...mentioning
confidence: 99%
See 1 more Smart Citation